Rehabilitation Management for Sarcopenia in Chronic Obstructive Pulmonary Disease: A Literature Review - Widjanantie, Siti Chandra; Lestari, Fiona; Nusdwinuringtyas, Nury; Susanto, Agus Dwi (Respiratory Science, 2024)
Chronic obstructive pulmonary disease (COPD) is a prevalent and debilitating chronic respiratory condition that not only affects the lungs but has far-reaching systemic consequences; one such consequence is the heightened risk of developing sarcopenia, a condition characterized by progressive loss of skeletal muscle mass and strength. Recent studies have highlighted the significant prevalence of sarcopenia among COPD patients, with rates ranging from 7.9% to 66.7%. This association underscores the importance of early identification and intervention to mitigate the adverse outcomes related to both conditions. Managing COPD patients with sarcopenia is fraught with challenges, primarily due to the multifaceted nature of both conditions. Sarcopenia exacerbates the decline in respiratory function and physical performance in COPD patients, complicating treatment and management strategies. The complexity is further amplified by the need for personalized treatment plans that address these conditions' pulmonary and musculoskeletal aspects. Precise assessment and re-evaluation are essential to ensure optimal outcomes and enhance physical and functional well-being. Rehabilitation for COPD patients with sarcopenia involves a multidisciplinary approach, focusing on exercise training, nutritional support, and pulmonary interventions. Pulmonary rehabilitation programs, tailored to individual patient needs and capabilities, have shown promise in improving exercise capacity, functional performance, and overall health status, thereby enhancing the quality of life for these patients.  In this literature review, we will discuss the elevated risk of sarcopenia in COPD patients, highlight the significance of rehabilitation management, and emphasize the pivotal role of precise assessment and re-evaluation in optimizing the care provided to this population.